Петро Іванович Баранський (до 90-рiччя вiд дня народження) - Belyaev, O. Ye.; Valakh, M. Ya.; Venger, Ye. F.; Klad’ko, V. P.; Kochelap, V. O.; Litovchenko, V. G.; Lysenko, V. S.; Syzov, F. F.; Babych, V. M.; Dmytruk, M. L.; Kolomoets, V. V.; Konakova, R. V.; et al. (Publishing house "Academperiodika", 2019)
-